STUDI TENTANG KEKERASAN SEKSUAL YANG DILAKUKAN MELALUI PEMBESARAN ALAT KELAMIN - Salamor, Anna Maria; Latupeirissa, J.E.; Hehanussa, D.J.A.; Salamor, Y. B. (Faculty of Law, Universitas Pasundan, 2021)
Violence against women is a global phenomenon that is not affected by racial or ethnic boundaries, culture and social class. One form of violence against women is sexual violence. Sexual violence is a form of violence that can occur in both public and domestic spheres. The legal subjects of perpetrators of sexual violence are usually suffered by women and children who are often seen as weak victims. One form of sexual violence against women is to enlarge the genitals. The problem in this study is whether genital enlargement can be qualified as sexual violence. The research method used is normative juridical. Husband and wife relationship is a fun sexual activity between partners. The concept of masculinity and self-esteem which is shown by the symbolism of the size of the genitals and high sexual ability can lead to sexual violence between partners. In some cases, enlargement of the genitals (penis) is done without the wife (partner) knowing. When penetration occurs and causes a painful feeling, the wife (partner) realizes that the husband's genitals have been enlarged. On the other hand, when the pain arises during penetration, the wife asks to stop or stop for a moment but is ignored and is still forced to penetrate until they are finished. Enlargement of the genitals accompanied by force during intercourse is a form of sexual violence, however it is still considered taboo in domestic life because the wife is ashamed of the public's scrutiny if it is reported to the police. Keyword: Genitals; Violence; Sexual.